Biofertilizer potentials of Rhizobium leguminosarum on two common tropical vegetable plants Talinium triangulare (waterleaf) and Telfairia occidentalis (pumpkin) - Eze, V C; Okoronkwo, E C; Ngene, A C; Odo, E S (Bangladesh Journal of Scientific and Industrial Research, 2023)
This study explored the biofertilizer capabilities of Rhizobium leguminosarum on two tropical vegetables, Talinum triangulare (waterleaf) and Telfairia occidentalis (pumpkin). The microorganisms were isolated, characterized, and inoculated onto activated charcoal carriers at varying concentrations for each vegetable, with controls using sterile activated charcoal and N.P.K fertilizer. After 28 days, growth indices including plant biomass, height, and mean leaf area were evaluated. Results showed significant growth improvements with Rhizobium leguminosarum, ranging from 107.77% to 286.78% for waterleaf and 166.52% to 358.26% for pumpkin, surpassing N.P.K fertilizer. Leaf areas also increased significantly, with Rhizobium-inoculated vegetables outperforming chemically fertilized ones. While the impact on plant height was relatively lower, this research highlights the potential of Rhizobium leguminosarum as a fertilizer for enhancing waterleaf and pumpkin growth. Future studies should expand on these findings in different vegetable types and environmental conditions to validate real-world field applications. Bangladesh J. Sci. Ind. Res. 58(4), 231-240, 2023